2008
DOI: 10.1088/0004-637x/690/1/20
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistent Models of the Agn and Black Hole Populations: Duty Cycles, Accretion Rates, and the Mean Radiative Efficiency

Abstract: We construct evolutionary models of the populations of active galactic nuclei (AGN) and supermassive black holes, in which the black hole mass function grows at the rate implied by the observed luminosity function, given assumptions about the radiative efficiency and the luminosity in Eddington units. We draw on a variety of recent X-ray and optical measurements to estimate the bolometric AGN luminosity function and compare to X-ray background data and the independent estimate of Hopkins et al. (2007) to asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

91
715
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(826 citation statements)
references
References 164 publications
91
715
14
Order By: Relevance
“…Our work strongly supports the picture of BH mass downsizing or 'anti-hierarchical' BH growth, suggested by previous studies (Merloni 2004;Heckman et al 2004;Shankar et al 2009;Vestergaard & Osmer 2009;Shen & Kelly 2012;Nobuta et al 2012). The downsizing in the AGN LF is driven by mass downsizing and by a change of the accretion rate distribution function with time, suggesting a complex process driving the cosmic evolution of BH growth.…”
Section: Discussionsupporting
confidence: 90%
“…Our work strongly supports the picture of BH mass downsizing or 'anti-hierarchical' BH growth, suggested by previous studies (Merloni 2004;Heckman et al 2004;Shankar et al 2009;Vestergaard & Osmer 2009;Shen & Kelly 2012;Nobuta et al 2012). The downsizing in the AGN LF is driven by mass downsizing and by a change of the accretion rate distribution function with time, suggesting a complex process driving the cosmic evolution of BH growth.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are comparable to Mullaney et al (2012), in which the SFR within 1 z < 2 bin is 3.5 times greater than within z < 1 bin, while the SFR when z > 2 is 10.3 times greater than when z < 1. Because the AGN activity and star formation are known to peak at z ∼ 2 (e.g., Shankar et al 2009;Behroozi et al 2013;Burgarella et al 2013;Delvecchio et al 2014), we then fit the SFR as a function to the redshift within z < 2 and z 2 separately. Besides the rapidly increasing SFR when z < 2, we also see a slight decrease toward higher redshifts at z > 2.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent mass measurements of the local nuclear MBHs suggested that the MBH mass density in the local Universe is consistent with the accreted mass inferred by integrating the quasar luminosity function at all redshifts assuming ≈ 0.1 [20,[87][88][89][90]. Therefore, the "quasar mode," in which large amount of gas are accreted in single coherent episodes via accretion disks shining close to the Eddington luminosity, appears to be principal path of MBH cosmic growth.…”
Section: The Making Of the Giants: Massive Black Hole Accretion Historymentioning
confidence: 65%
“…Different fits to the Kα line in MCG-6-30-15 gave a > 0.98 [167], a = 0.86±0.01 [165], and a = 0.49 +0. 20 −0.12 [164]. Even more problematic is the case of NGC 3783, for which different groups found a > 0.88 [168] and a < 0.32 [164].…”
Section: Spin Evolutionmentioning
confidence: 98%